Bildmedien Festschrift für Klaus Sachs-Hombach zum 65. Geburtstag - Thon, Jan-Noël; Berndt, Frauke (De Gruyter, 2022)
This volume brings together a selection of contributions on the forms and functions of both contemporary and historical visual media. It aims to bring a range of perspectives from philosophical, cultural studies, and media studies on the materiality, semiotics, and aesthetics of images and other visual media forms into productive dialogue with each other.